Mentalitas Pencari Riba: Di Antara Perspektif Birokrat Pemerintah Vs Max Weber (Studi Teoritis Menggunakan Input-Output dan Hasil) - Edward Sitepu; Slamet Triadi; K. Dhwi Waspodo (STT INTI Bandung, 2023)
Max Weber's research in the 20th century regarding bureaucratic government was carried out by paying attention to the work ethic (outside and usability). Using the entities of efficiency and effectiveness, Weber termed the ideal bureaucracy. And of course the gate of achievement is selection. Weber argues, the right and correct selection will develop a long-term career in the company by giving them job security and performance-based rewards. What about the current condition, seen from the many cases of corruption in government institutions? This article reviews the virtues of external bureaucratic apparatus so as not to show a hedonic attitude stemming from usury-seeking activities. That is, the knowledge that underpins rational action is a causal property understood in terms of means-end relations, aspiring toward a logically interconnected and systematic whole. It is in this segment that serious and measurable improvements should be needed.